Composite separator and method for manufacturing the same
Patent Information
- Application Number
- CN202611165380.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这类聚烯烃隔膜存在明显缺陷:高温下热收缩严重,易导致正负极直接接触引发局部短路和热失控,带来巨大安全隐患;同时,聚烯烃材料本身的疏液特性使其对极性电解液的浸润性较差,导致离子电导率降低、耐穿刺性能不足,这些问题已成为锂电池高性能化过程中亟待克服的瓶颈
本发明通过在PTFE基膜表面形成陶瓷涂层,其中粘结剂和陶瓷填料掺入PTFE高温隔膜中,因为粘结剂和陶瓷填料对电解液的浸润性更好,因此与PTFE膜结合后,可以获得浸润性优良的复合隔膜;
Smart Images

Figure CN123018353A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery separator technology, and in particular to a composite separator and its preparation method. Background Technology
[0002] As a key component of lithium-ion batteries, the separator's overall performance directly affects the battery's cycle stability, safety performance, and tolerance to high-temperature conditions.
[0003] Currently, commercially available battery separators are mainly made of polypropylene (PP) and polyethylene (PE) microporous membranes. However, these polyolefin separators have significant drawbacks: severe thermal shrinkage at high temperatures can easily lead to direct contact between the positive and negative electrodes, causing localized short circuits and thermal runaway, posing a huge safety hazard; at the same time, the hydrophobic properties of polyolefin materials themselves result in poor wettability to polar electrolytes, leading to reduced ionic conductivity and insufficient puncture resistance. These problems have become bottlenecks that urgently need to be overcome in the process of achieving high performance in lithium batteries.
[0004] PTFE separators possess excellent thermal stability (high temperature resistance), low impedance, and outstanding safety performance, effectively avoiding the thermal shrinkage problem of polyolefin separators under high-temperature conditions. However, PTFE materials also face the challenge of poor electrolyte wettability, a characteristic that limits the cycle performance and interfacial stability of batteries, thus requiring further optimization and improvement. Summary of the Invention
[0005] To address the aforementioned problems, this invention discloses a composite diaphragm and its preparation method. The technical solution of this invention is implemented as follows: The first aspect of the present invention discloses a composite membrane, the composite membrane comprising a PTFE base membrane and a ceramic coating disposed on at least one side of the PTFE base membrane, the ceramic coating comprising an organic solvent, a binder, and a ceramic filler; The adhesive includes hydrogenated nitrile butadiene rubber; The ceramic filler includes hydrophobic fumed silica. 。
[0006] Furthermore, the thickness of the ceramic coating is 10μm-100μm.
[0007] Furthermore, the hydrophobic fumed silica (SiO2) is chemically modified by a modifier, which includes at least one of dimethyldichlorosilane, trimethylchlorosilane, and hexamethyldisilazane.
[0008] Furthermore, the organic solvent includes at least one of ketone solvents, ester solvents, aromatic hydrocarbon solvents, and amide solvents.
[0009] Furthermore, the PTFE base film has a thickness of 5μm-30μm, a pore size of 0.2μm-15μm, and a porosity of 80%-95%.
[0010] Further, by weight, the amount of the adhesive is 1 to 5 parts and the amount of the organic solvent is 20 to 80 parts.
[0011] Furthermore, based on a total mass of 100 wt% for the binder and the organic solvent, the mass percentage of the ceramic filler is 0.01% to 10%.
[0012] A second aspect of this invention discloses a method for preparing a composite membrane, the method comprising the following steps: S1, Add the adhesive to the organic solvent and stir until completely dissolved to obtain the first mixed solution; S2, add ceramic filler to the first mixed solution, mix and stir evenly to obtain a second mixed solution; S3, the second mixed solution is applied to the substrate to form a wet coating; S4, cover the surface of the wet coating away from the substrate with a PTFE base film; S5. After drying, the substrate is peeled off to obtain a composite diaphragm.
[0013] Furthermore, in step S2, the viscosity of the second mixed solution is 1000 mPa·s to 2000 mPa·s.
[0014] Furthermore, the substrate mentioned in step S3 is selected from at least one of aluminum foil, copper foil, PET film, PTFE film and glass.
[0015] Beneficial technical effects of the present invention: This invention forms a ceramic coating on the surface of a PTFE base membrane, wherein a binder and ceramic filler are incorporated into the PTFE high-temperature separator. Because the binder and ceramic filler have better wettability to the electrolyte, a composite separator with excellent wettability can be obtained after being combined with the PTFE membrane. HNBR itself has high strength. Hydrophobic gaseous SiO2, as a nanofiller, is uniformly dispersed and further strengthened through physical interactions (the organic groups on the surface of SiO2 are similar to the hydrocarbon chain structure of HNBR, and form tight connections through hydrophobic effects and van der Waals forces) and interfacial hydrogen bonding (the silanol groups remaining on the surface of SiO2 can also form hydrogen bonds with the nitrile groups or unsaturated double bonds in the HNBR molecular chain). The saturated structure of HNBR itself gives it excellent heat resistance, while SiO2 has high thermal stability. At high temperatures, SiO2 can also restrict the movement of HNBR molecular chains, thereby reducing the decline in mechanical properties caused by thermal expansion. Furthermore, this invention employs organosilane modifiers (such as dimethyldichlorosilane, trimethylchlorosilane, and hexamethyldisilazane) to hydrophobically modify gaseous SiO2. After modification, hydrophobic groups are grafted onto the surface of the particles, which can reduce the affinity for polar impurities, thereby reducing the intrusion of impurities such as water in the electrolyte, inhibiting the decomposition and side reactions of the electrolyte, and improving the long-term stability of the battery. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only one embodiment of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a SEM image (outer surface) of the composite diaphragm of Embodiment 1 of the present invention at 10K magnification. Figure 2 This is a SEM image (inner side) of the composite diaphragm of Embodiment 1 of the present invention at 10K magnification. Figure 3 for Figure 2 The EDS layered image shown; Figure 4 This is a contact angle test diagram from Example 1; Figure 5 The image shows the contact angle test results for Comparative Example 1. Detailed Implementation
[0018] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0019] In the description of this invention, it should be understood that the orientation descriptions, such as up, down, front, back, left, right, etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.
[0020] In the description of this invention, "several" means one or more, "multiple" means two or more, "greater than," "less than," and "exceeding" are understood to exclude the stated number, while "above," "below," and "within" are understood to include the stated number. The use of "first" and "second" in the description is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, or implicitly indicating the number of indicated technical features, or implicitly indicating the order of the indicated technical features.
[0021] In the description of this invention, unless otherwise explicitly defined, terms such as "set up," "install," and "connect" should be interpreted broadly, and those skilled in the art can reasonably determine the specific meaning of the above terms in this invention in conjunction with the specific content of the technical solution.
[0022] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0023] To overcome the defect of poor electrolyte wettability of PTFE material, this invention proposes a technical solution.
[0024] The first aspect of the present invention discloses a composite membrane, the composite membrane comprising a PTFE base membrane and a ceramic coating disposed on at least one side of the PTFE base membrane, the ceramic coating comprising an organic solvent, a binder, and a ceramic filler; The adhesive includes hydrogenated nitrile butadiene rubber; The ceramic filler comprises hydrophobic vapor phase SiO2.
[0025] On the one hand, the main chain of hydrogenated nitrile butadiene rubber (HNBR) is highly saturated, retaining only a small amount or no carbon-carbon double bonds, while the side chains contain polar cyano groups (-CN). The highly saturated main chain reduces the activity of the molecular chain and inhibits the interaction with non-polar solvents. On the other hand, the polar cyano groups make HNBR compatible with polar solvents, helping the electrolyte to penetrate and distribute evenly, which is beneficial for ion transport.
[0026] Furthermore, the binder and ceramic filler form a robust three-dimensional network, enhancing stability. This maintains the mechanical strength and toughness of the PTFE base film and inhibits the shedding of non-conductive particles from the PTFE base film during lithium battery winding.
[0027] On the other hand, the hydrophobic vapor-phase SiO2 surface undergoes chemical modification to reduce the number of silanol groups and introduce organic groups. These organic groups significantly improve its compatibility with solvents, regulate interfacial wettability, and reduce surface tension, making it easier for solvents to spread on the surface and enabling rapid and uniform wetting and dispersion. Compared to hydrophilic vapor-phase SiO2, the organic groups on the surface of hydrophobic vapor-phase SiO2 effectively block water molecule adsorption, avoiding particle agglomeration, slurry thickening, or gelation caused by water absorption, thereby significantly improving the long-term dispersion stability and processing uniformity of the slurry.
[0028] Hydrophobic gaseous SiO2 particles have a chain-like or aggregated structure. In the dispersion solvent system, the particles form a three-dimensional network structure through physical adsorption or chemical bonding, constructing an effective thixotropic network, which increases the viscosity of the slurry.
[0029] The surface of vapor-phase SiO2 can adsorb lithium ions, promoting the uniform distribution of lithium ions at the separator / electrolyte interface, reducing local lithium deposition, and helping to suppress lithium dendrite growth.
[0030] In some specific embodiments, the thickness of the ceramic coating is 10 μm to 100 μm.
[0031] Excessive thickness increases the mass and volume of the composite separator, thus affecting the battery's energy density; insufficient thickness leads to incomplete wetting, also impacting the composite separator's performance. Therefore, controlling the thickness within 10μm-100μm yields a composite separator that balances battery energy density and wettability. For example, the thickness of the ceramic coating can be selected from 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, etc.
[0032] In some embodiments, the hydrophobic vapor phase SiO2 is chemically modified by a modifier, which includes at least one of dimethyldichlorosilane, trimethylchlorosilane, and hexamethyldisilazane.
[0033] The Si-Cl or Si-N bonds of the above-mentioned modifiers readily react with the surface silanol groups, introducing hydrophobic groups such as dimethylsiloxy or trimethylsiloxy, respectively, to achieve hydrophobicity.
[0034] Surface hydrophobic groups can reduce the affinity for polar impurities, thereby reducing the intrusion of impurities such as water in the electrolyte and reducing electrolyte decomposition and side reactions.
[0035] In this application, hydrophobic gaseous SiO2 is surface modified by an organosilane modifier. The modification reaction can reduce the density of surface silanol groups, but some silanol groups remain, providing interaction sites for subsequent hydrogen bonding with the binder.
[0036] In some embodiments, the organic solvent includes at least one of ketone solvents, ester solvents, aromatic hydrocarbon solvents, and amide solvents.
[0037] In some specific embodiments, the ketone solvents include, but are not limited to, ethyl methyl ketone (methyl ethyl ketone) and cyclohexanone; the ester solvents include, but are not limited to, ethyl acetate, butyl acetate, and triethyl phosphate; the aromatic hydrocarbon solvents include, but are not limited to, benzene and toluene; and the amide solvents include, but are not limited to, N-methylpyrrolidone and N,N-dimethylformamide.
[0038] In this invention, when the binder is HNBR, suitable organic solvents include ketones, esters, aromatic hydrocarbons, and amides. However, HNBR dissolves slowly in amide solvents such as NMP and DMF, and is prone to excessive swelling in ketone and ester solvents, affecting the coating effect.
[0039] Preferably, the organic solvent compatible with HNBR in this application is triethyl phosphate.
[0040] Specifically, triethyl phosphate (TEP) can effectively dissolve HNBR and has excellent compatibility with hydrophobic gas phase SiO2 to form a uniform and stable coating slurry. At the same time, the flame-retardant properties of TEP help improve the safety performance of the battery. Therefore, triethyl phosphate (TEP) is preferred as an organic solvent.
[0041] In some specific embodiments, the PTFE base film has a thickness of 5μm to 30μm, a pore size of 0.2μm to 15μm, a porosity of 80% to 95%, and a tensile strength of 10MPa to 30MPa.
[0042] In specific applications, the thickness of the PTFE base film can be selected from 5μm, 6μm, 7μm, 8μm, 10μm, 12μm, 13μm, 15μm, 16μm, 18μm, 20μm, 22μm, 23μm, 25μm, 26μm, 28μm, 30μm, etc.; the pore size can be selected from 0.2μm, 0.4μm, 0.5μm, 0.8μm, 1μm, 2μm, 5μm, 6μm, 7μm, 8μm, 10μm, 12μm, 13μm, 15μm, etc.; the porosity can be selected from 80%, 82%, 83%, 84%, 85%, 88%, 90%, 91%, 92%, 95%, etc.; and the tensile strength can be selected from 10MPa, 15MPa, 20MPa, 25MPa, 30MPa, etc.
[0043] The above examples are merely illustrative and not intended to limit the scope of understanding. Those skilled in the art are free to implement any of the values within the above range without exceeding their own understanding.
[0044] In some embodiments, the amount of the adhesive is 1 to 5 parts by weight, and the amount of the organic solvent is 20 to 80 parts by weight.
[0045] In specific applications, the mass ratio of the adhesive to the organic solvent can be 1:20, 2:40, 3:60, 4:80, 5:80, etc. The above examples are merely illustrative and not limiting. Those skilled in the art are free to implement any values within the above ranges without exceeding their understanding.
[0046] In some specific embodiments of this application, the ratio of the adhesive to the organic solvent is 2:40 (i.e., 1:20).
[0047] In some embodiments, the ceramic filler accounts for 0.01% to 10% of the total mass of the binder and the organic solvent, which is 100 wt%.
[0048] In this invention, the mass percentage of the ceramic filler refers to the percentage of the mass of the ceramic filler relative to the sum of the masses of the binder and the organic solvent, calculated according to the following formula: Ceramic filler percentage (wt%) = [mass of ceramic filler / (mass of binder + mass of organic solvent)] × 100%.
[0049] In specific applications, the mass percentage of the ceramic filler can be selected as 0.01%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The above examples are merely illustrative and not limiting. Those skilled in the art can freely implement any value within the above range without exceeding their understanding.
[0050] A second aspect of this invention discloses a method for preparing a composite membrane, the method comprising the following steps: S1, Add the adhesive to the organic solvent and stir until completely dissolved to obtain the first mixed solution; S2, add ceramic filler to the first mixed solution, mix and stir evenly to obtain a second mixed solution; S3, the second mixed solution is applied to the substrate to form a wet coating; S4, cover the surface of the wet coating away from the substrate with a PTFE base film; S5. After drying, the substrate is peeled off to obtain a composite diaphragm.
[0051] In some embodiments, the stirring temperature in step S1 is 45℃~100℃, and the stirring time is 12h~14h.
[0052] In specific applications, the stirring temperature can be selected from 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, etc.; the stirring time can be selected from 12h, 12.5h, 13h, 13.5h, 14h, etc. The above examples are merely examples and are not limitations. Without exceeding the understanding of those skilled in the art, they are free to implement any values within the above ranges.
[0053] In some embodiments, the viscosity of the second mixed solution in step S2 is 1000 mPa·s to 2000 mPa·s.
[0054] In specific applications, the viscosity of the second mixed solution can be selected from 1000 mPa·s, 1200 mPa·s, 1400 mPa·s, 1600 mPa·s, 1800 mPa·s, 2000 mPa·s, etc. The above examples are merely illustrative and not limiting. Those skilled in the art are free to implement any value within the above range without exceeding their understanding.
[0055] In some embodiments, the substrate mentioned in step S3 includes one of aluminum foil, copper foil, PET film, PTFE film, and glass.
[0056] In some embodiments, the scraper height is set to 10μm~100μm during coating; the purpose of adjusting the scraper height is to control the thickness of the ceramic coating formed by coating. Optionally, the scraper height is 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, etc.
[0057] In some embodiments, the PTFE base film is covered on the wet coating on the side of the surface away from the substrate in step S4 mainly because the PTFE film itself is soft and easily deformed. Therefore, the second mixed solution, i.e., the slurry, needs to be coated on the substrate first, and then the PTFE high-temperature membrane is covered. In addition, some adhesives and ceramic fillers can be incorporated into the PTFE high-temperature membrane.
[0058] In some embodiments, step S5 drying is divided into a first drying and a second drying. The first drying is carried out at 60℃~100℃ for 2h~8h, and the second drying is carried out under vacuum at 40℃~80℃ for 12h~18h. This employs a step-by-step drying process of first air drying and then vacuum drying. The air drying can quickly remove most of the organic solvent in the coating layer at normal pressure and relatively high temperature, forming a pre-cured ceramic coating. The subsequent vacuum drying further removes residual trace amounts of solvent, avoiding adverse effects of solvent residue on the electrochemical performance of the membrane. Furthermore, the vacuum environment significantly reduces the drying temperature, minimizing thermal damage to the PTFE base film or binder, while preventing oxidation or side reactions of residual solvent at high temperatures, thus ensuring the structural integrity and interfacial stability of the composite membrane. Through the synergistic effect of these two drying steps, a composite membrane with a dense coating, good adhesion, and no swelling defects can be obtained while improving drying efficiency.
[0059] In practical applications, the first and second drying temperatures can be selected as 60℃, 70℃, 80℃, 90℃, 100℃, etc., and the time can be selected as 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc.; the second drying temperature can be selected as 40℃, 50℃, 60℃, 70℃, 80℃, etc., and the time can be selected as 12h, 13h, 14h, 15h, 16h, 17h, 18h, etc. The above examples are merely illustrative and not limiting. Those skilled in the art can freely implement any values within the above ranges without exceeding their understanding.
[0060] In some specific embodiments, considering the shrinkage of the slurry and the ease of peeling, the present invention preferably uses aluminum foil as the substrate.
[0061] The embodiments of the present invention will be described in more detail below through examples and comparative examples. It should be noted that the embodiments of the present invention are not limited to these examples.
[0062] In addition, to reduce errors, the preparation processes of the positive electrode, negative electrode, and electrolyte in the embodiments and comparative examples of this invention are exactly the same, and the battery assembly process is also the same. Example
[0063] I. Preparation of composite membrane: Two parts of hydrogenated nitrile rubber were added to 40 parts of triethyl phosphate and stirred at 80°C for 18 hours. After the first mixed solution was completely dissolved, 0.04 parts of hydrophobic fumed SiO2 were added and stirring was continued until a second mixed solution was formed with a viscosity of 1500 mPa·s. An appropriate amount of the uniformly mixed second mixed solution was coated onto an aluminum foil substrate, and the scraper height was adjusted to 25 μm. Then, a PTFE high-temperature diaphragm was covered on the surface of the second mixed solution. After drying in a forced-air oven at 60°C for 4 hours, vacuum drying was continued for 18 hours. After peeling off the substrate, the modified PTFE high-temperature diaphragm was obtained.
[0064] In this embodiment, the PTFE high-temperature diaphragm has a thickness of 15μm, an average pore size of 5μm, a porosity of 88%, and a tensile strength of 18MPa.
[0065] 2. Electrolyte preparation: In an argon glove box, LiPF6 was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) in a volume ratio of 1:1:1, and 2 wt.% of vinylene carbonate (VC) was added as an additive.
[0066] One sample of the composite membrane prepared in Example 1 was taken and photographed using SEM at 10K magnification. Figure 1 and Figure 2 The porous structure of the PTFE high-temperature membrane was shown; Figure 1 This refers to the outer surface of the composite diaphragm. Figure 2 The inner aluminum foil surface of the composite diaphragm has its holes flattened, making it smoother. Figure 3 The results of EDS analysis on the inner aluminum foil surface show that hydrophobic vapor phase SiO2 is incorporated into the PTFE high-temperature membrane and is widely distributed.
[0067] Ten additional composite membrane samples prepared in Example 1 were taken and their contact angles were tested using a contact angle tester. Figure 4 As shown, the process is as follows: (1) First, draw a portion of the electrolyte into the dropper to expel air bubbles from the liquid in the dropper. After expelling the air bubbles, draw another 100 μL of the measurement liquid. (2) Fix the sample on the sample stage, rotate the injector, and click semi-automatic fitting analysis after the droplet contacts the film surface (the side with the ceramic coating). After the analysis is completed, obtain the angle. Example
[0068] The preparation process in this embodiment is basically the same as that in Example 1, except that the height of the scraper is 50 μm in this embodiment.
[0069] After preparation, ten composite membrane samples prepared in Example 2 were taken for contact angle testing. The testing process and environment were exactly the same as in Example 1. Example
[0070] The preparation process in this embodiment is basically the same as that in Example 1, except that the height of the scraper is 10 μm in this embodiment.
[0071] After preparation, ten composite membrane samples prepared in Example 3 were taken for contact angle testing. The testing process and environment were exactly the same as in Example 1. Example
[0072] The preparation process in this embodiment is basically the same as that in Example 1, except that the height of the scraper is 100 μm in this embodiment.
[0073] After preparation, ten composite membrane samples prepared in Example 4 were taken for contact angle testing. The testing process and environment were exactly the same as in Example 1. Example
[0074] The preparation process in this embodiment is basically the same as that in Example 1, except that the height of the scraper is 5 μm in this embodiment.
[0075] After preparation, ten composite membrane samples prepared in Example 5 were taken for contact angle testing. The testing process and environment were exactly the same as in Example 1. Example
[0076] The preparation process in this embodiment is basically the same as that in Example 1, except that the height of the scraper is 150 μm in this embodiment.
[0077] After preparation, ten composite membrane samples prepared in Example 6 were taken for contact angle testing. The testing process and environment were exactly the same as in Example 1.
[0078] Comparative Example 1: Electrolyte preparation: In an argon glove box, LiPF6 was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and 2 wt.% of vinylene carbonate (VC) was added as an additive.
[0079] In this comparative example, the thickness of the PTFE membrane was selected to be the same as that of the PTFE base membrane in Example 1, which was 15 μm.
[0080] After preparation, ten diaphragm samples prepared in Comparative Example 1 were taken for contact angle testing. Figure 5 As shown, the testing process and environment are exactly the same as in Example 1.
[0081] The average of the contact angle test results from Examples 1-6 and Comparative Example 1 is summarized in the table below.
[0082]
[0083] As shown in the table above, the contact angle of Example 1 (66.1°) is much smaller than that of Comparative Example 1 (100.6°), indicating that the electrolyte wettability of the composite membrane is significantly improved. Combined with the EDS spectrum, the lower contact angle of the inner aluminum foil surface (B-side) may be related to the hydrophobic vapor-phase SiO2 enriched on this surface, further verifying its role in improving wettability. In summary, this application significantly improves the electrolyte wettability of the membrane by setting a ceramic coating containing HNBR and hydrophobic vapor-phase SiO2 on the surface of the PTFE base membrane.
[0084] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite diaphragm, characterized in that, It includes a PTFE base film and a ceramic coating disposed on at least one side of the PTFE base film, wherein the ceramic coating includes an organic solvent, a binder, and a ceramic filler; The adhesive includes hydrogenated nitrile butadiene rubber; The ceramic filler comprises hydrophobic fumed silica.
2. The composite diaphragm according to claim 1, characterized in that, The thickness of the ceramic coating is 10μm to 100μm.
3. The composite diaphragm according to claim 1, characterized in that, The hydrophobic fumed silica is chemically modified by a modifier, which includes at least one of dimethyldichlorosilane, trimethylchlorosilane, and hexamethyldisilazane.
4. The composite diaphragm according to claim 1, characterized in that, The organic solvent includes at least one of ketone solvents, ester solvents, aromatic hydrocarbon solvents, and amide solvents.
5. The composite diaphragm according to claim 1, characterized in that, The PTFE base film has a thickness of 5μm to 30μm, a pore size of 0.2μm to 15μm, and a porosity of 80% to 95%.
6. The composite diaphragm according to claim 1, characterized in that, The amount of the adhesive is 1 to 5 parts by weight, and the amount of the organic solvent is 20 to 80 parts by weight.
7. The composite diaphragm according to claim 1, characterized in that, Based on a total mass of 100 wt% for the binder and the organic solvent, the ceramic filler accounts for 0.01% to 10% of the total mass.
8. A method for preparing a composite diaphragm, characterized in that, The steps include the following: S1, Add the adhesive to the organic solvent and stir until completely dissolved to obtain the first mixed solution; S2, add ceramic filler to the first mixed solution, mix and stir evenly to obtain a second mixed solution; S3, the second mixed solution is applied to the substrate to form a wet coating; S4, cover the surface of the wet coating away from the substrate with a PTFE base film; S5. After drying, the substrate is peeled off to obtain a composite diaphragm.
9. The method for preparing the composite diaphragm according to claim 8, characterized in that, In step S2, the viscosity of the second mixed solution is 1000 mPa·s to 2000 mPa·s.
10. The method for preparing the composite diaphragm according to claim 8, characterized in that, The substrate mentioned in step S3 is selected from at least one of aluminum foil, copper foil, PET film, PTFE film and glass.
